The origins and dynamics of export superstars - Caroline L. Freund; Martha Denisse Pierola (Inter-American Development Bank (IDB), 2016)
This paper uses firm-level data on manufacturing trade from 40 developing countries to explore how the five largest exporters in a country contribute to export growth and diversification. The origins of these firms are also studied. The data show that the top five exporters account for on average one third of exports, over half of export growth, and almost all of export diversification over a five-year period. Controlling for country and industry fixed effects, the share of exports in the top five firms increases significantly as exports grow. Most top five exporters were already large five years ago or are new firms; it is extremely rare for these export superstars to emerge from the bottom half of the firm-size distribution. They are producers, not traders, and are primarily foreign owned.
Keywords: D22; L11; L25; F14; 330; Firm size distribution; power law; comparative advantage; export growth